Hubungan Status Gizi (IMT/U), Asupan Natrium, dan Kalium dengan Hipertensi pada Remaja di SMAN 10 Tangerang Tahun 2022 - Amalia Maulida (2022)
Hypertension or high blood pressure is when the blood pressure in the arteries increases. Adolescents defined as hypertension were those with systolic and diastolic blood pressure in the 95th percentile based on age, height, and sex, measured at least under 3-5 minutes of rest. According to the Basic Health Research (Riskesdas) in 2018, the prevalence of hypertension in Indonesia is 34.1%. The prevalence of hypertension in Banten Province is 29.47% and in Tangerang City is 28.74%, based on Riskesdas 2018. This study aims to analyze the relationship between nutritional status, sodium intake, and potassium with the incidence of hypertension in adolescents at SMAN 10 Tangerang. The research is Quantitative research that uses a "cross-sectional" study design with a sample size of 69 respondents using a simple random sampling method in May 2022. The results of the bivariate test with chi-square indicate that there is a relationship between nutritional status (p = 0,03; OR = 6,600) and sodium intake (p = 0,022; OR = 5,308) with the incidence of hypertension in adolescents. Meanwhile, potassium intake (p=0,303) did not show any relationship with the incidence of hypertension in adolescents. Keywords : Hypertension, Sodium, Potasium, Adolescents, Nutrition Status.